ANALISIS DATA MINING PADA PEMILIHAN JENIS GAME TERPOPULER MENGGUNAKAN ALGORITMA APRIORI: Indonesia - Muhammad Alwi; Ninis Anggraini; Rodia (ITP Press, 2023)
Game is one of the entertainment that is often chosen by the general public to fill their free time. The game itself has different types and according to the interests of the community to play the game. Examples of types of games in general include MOBA, Strategy, RPG and several other types of games that are often played by the public, especially game fans. In this study, we will focus on the types of games that are very popular among the public by using the a priori algorithm as an analytical method. The Apriori algorithm was chosen because it can determine the shape of the pattern in the types of games that are of interest so that the results of this study will be useful for the game sales industry in determining the types of games to be sold at game stores and game sales platforms. This study will use a minimum support value of 50% and a minimum confidence of 70% and the results of the analysis show that the types of games from Action, Adventure and RPG are the most popular game types and have a confidence value of 82% compared to RPG game types. , Strategy and Battle with a confidence value of 74%. These results indicate that the a priori algorithm will greatly help make it easier to find out the most popular type patterns based on the values ​​of the frequent items that have been analyzed.